2012
DOI: 10.1021/jm300975f
|View full text |Cite
|
Sign up to set email alerts
|

Systematic in Vivo Screening of a Series of 1-Propyl-4-arylpiperidines against Dopaminergic and Serotonergic Properties in Rat Brain: A Scaffold-Jumping Approach

Abstract: A series of 1-propyl-4-arylpiperidines were synthesized and their effects on the dopaminergic and serotonergic systems tested in vivo and in vitro. Scaffold jumping among five- and six-membered bicyclic aryl rings attached to the piperidine ring had a marked impact on these effects. Potent and selective dopamine D(2) receptor antagonists were generated from 3-indoles, 3-benzoisoxazoles, 3-benzimidazol-2-one, and 3-benzothiophenes. In contrast, 3-benzofuran was a potent and selective inhibitor of monoamine oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…in living cells. [53][54][55][56] Moreover, previous studies have suggested that methoxy group played a key role in the interaction between several FDA-approved EGFR inhibitors (e.g. erlotinib, getinib, brigatinib and osimertinib) and EGFR.…”
Section: Chemical Sciencementioning
confidence: 99%
“…in living cells. [53][54][55][56] Moreover, previous studies have suggested that methoxy group played a key role in the interaction between several FDA-approved EGFR inhibitors (e.g. erlotinib, getinib, brigatinib and osimertinib) and EGFR.…”
Section: Chemical Sciencementioning
confidence: 99%
“…Piperazine is a privileged heterocyclic ring system present in a number of therapeutic agents with diverse pharmacological activities . In particular, N ‐arylpiperazines are found in a wide variety of small molecules binding to a diverse range of therapeutically relevant protein targets from enzymes, such as monoamine oxidase A (MAO−A) and B (MAO−B), to G protein‐coupled receptors (GPCRs), such as dopamine and serotonin receptors …”
Section: Introductionmentioning
confidence: 99%
“…Indole-, pyrrole-, and coumarin-containing therapeutic agents served as the inspiration for our studies. For example, RU24969, [14] phenprocoumon, and tipranavir are attractive medicinal targets which may benefit from nitrimine cross-coupling chemistry (Figure 1). With these targets in mind, the scope of reactions between various nitrimine electrophiles and coupling partners was explored.…”
mentioning
confidence: 99%